“Question Container” Game to Improve Arabic Writing Ability for Beginner Learners - Marsiah Fachri (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2015)
Language skill contains listening, speaking, reading and writing. It’s well known that teacher often gives the lesson about structure instead of writing skill. Whereas learning Arabic language is obligated to be able to write Arabic well. During learning in the class, teachers are monotonous and the students often lose their spirit, especially in Arabic lesson. “Stoppered Jar Ask Method” is a relax and exciting method of learning. Students can get the class with communicative, creative and pleasure condition and using contextual learning. This writing is the result of Classroom Action research. It means an action intentionally appeared and happens in a class at the same time. It’s divided by two cycles. At first cycle and second cycle, the lesson is about occupation or job ( AlMihnah ). The subject in this research is the beginner of Arabic Leaner at one of Islamic Junior High School at grade VIII, 2014/2015. From the result of this research, student is increasingly interested in Writing Arabic Skill through this method about 24, 90 %. At first cycle, the writing ability for student is about 66,94, it increases to be 74,17 at second cycle. And it happens in all aspects of writing skill. According toresult of direct observation during teaching and learning and dialogue at first and second cycle, students believe that writing by this method is very interesting and exciting. And it influences them to be active and enthusiasm student and has a high self confidence in writing Arabic.